Impacts of health services on agricultural labor productivity of rural households in Burkina Faso - Combary, Omer S. (International Food Policy Research Institute, 2016)
This article uses an instrumental variables method to evaluate the impact of the use of health services on the productivity of rural households’ farming labor in Burkina Faso. The distance from a household’s homestead to the Health and Social Promotion Center (HSPC) is considered an instrumental variable. The results reveal that using an HSPC in the case of an unexpected illness during the rainy season significantly improves farming labor productivity by FCFA 3170.5880 per man-day. In terms of policy implications for improving agricultural productivity, decision-makers should focus on the availability and quality of HSPC services in rural areas.